(untitled) (The Pakistan Development Review, 2012)
This paper analyses country-specific and industry-specific determinants of intra-industry trade (IIT) between Pakistan and other SAARC countries using panel data techniques. This paper also disentangles total IIT into horizontal and vertical IIT. The Vertical IIT is further divided into high-quality and low quality IIT. This paper finds that country-specific variables are more important in explaining the IIT relative to industry-specific variables. The decomposition of IIT shows that in the SAARC region Pakistan’s IIT is mostly comprised of the vertical IIT. The share of horizontal IIT is comparatively less. The paper offers specific policy recommendations for the promotion of IIT in the SAARC region. JEL classification: F12, F14, F15 Keywords: IIT, Horizontal IIT, Vertical IIT